A STUDY ON FUTURE OF MOBILE BASED PAYMENT FOR GOVERNMENT SERVICES IN INDIA - Jaiswal, Ashish (International Journal of Research -GRANTHAALAYAH, 2020)
Digital India programme of Government of India has promoting and encouraging the usage of digital payments for the various goods and services being availed by the citizens. The Government wants to develop a Digitally Empowered economy through the cashless transactions. As far as government agencies are concerned, mobile based payment is a noteworthy development on various domains, because it is going to increase ease and productivity for both the agencies and citizens themselves. Citizens who are using the Government services are concerned of the privacy of the data and information. Government needs to evaluate the procedure from beginning to end to ensure it meets strict standards and keeps information private. Poor literacy levels are a problem with this technology. The mobile payment services have to be effective in terms of usability, cost, efficiency, interoperability and security for transactions of all categories of citizens. Mobile payments options needs to be available even on low end mobile handsets.